Analysis of Relationships and Causality between Consumer Price Index (CPI), the Producer Price Index (PPI) and Purchasing Manager’s Index (PMI) in South Africa - Meyer, Daniel Francois; Habanabakize, Thomas (Journal of Economics and Behavioral Studies, 2018)
The variables the consumer price index (CPI), the producer price index (PPI) and the purchasing managers’ index (PMI) and play major roles in economic forecasting. The overall objective of this study is to assess the inter-relationships between CPI, PPI and PMI as predicting variables. This study is quantitative in nature and employed an ARDL econometric model, error correction model (ECM) and Granger causality approaches to establish long and short-run relationships. The ARDL method was used due to the fact that the variables had a mix of stationarity at levels I (0) and the first difference I (1). Quarterly datasets were obtained from Statistics South Africa (Stats SA) and the Bureau of Economic Research (BER) for the period 2000 to 2017. Results from the estimations discovered that variables cointegrate in the long-run. Additionally, evidence of short-run relationships has been determined using ECM. Furthermore, causal relationships were also analysed with results indicating that CPI causes PMI and PPI causes PMI. The implication of the research is the confirmation of the importance of relationships between CPI, PPI and PMI, which is especially significant in the short-run and the three index indicators are important macro-economic indicators for changes in overall economic activity on a macro level.